2016
DOI: 10.1186/s13068-016-0671-2
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma for lipid productivity in green microalgae: importance of substrate provision in improving oil yield without sacrificing growth

Abstract: Rising oil prices and concerns over climate change have resulted in more emphasis on research into renewable biofuels from microalgae. Unlike plants, green microalgae have higher biomass productivity, will not compete with food and agriculture, and do not require fertile land for cultivation. However, microalgae biofuels currently suffer from high capital and operating costs due to low yields and costly extraction methods. Microalgae grown under optimal conditions produce large amounts of biomass but with low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 138 publications
(195 reference statements)
0
59
1
Order By: Relevance
“…These results contradict the overflow hypothesis (OH), which postulates that the overflow of photo-synthase is the main driver of lipid and/or starch accumulation and is frequently discussed to explain increased carbon storage in photosynthetic microbes under stress conditions (Juergens, Disbrow, & Shachar-Hill, 2016; Neijssel & Tempest, 1975; Tan & Lee, 2016): indeed, substantial compromise in PSII activities at both transcriptional and phenotypic levels at early growth phase and the upregulation of enzymes associated with the accumulation of lipid throughout entire growth stages clearly suggest that the overflow of organic photo-synthase ab initio was not the main driver of high lipid accumulation under salinity stress. Rather, our results identified the pulling of the acetyl-CoA precursor generated from glycolysis towards lipid synthesis as a major driver of lipid accumulation; accordingly, the redirection of storage carbon likely resulted in the seeming conversion of carbohydrate to lipid as observed in the proximate analysis of harvested biomass.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…These results contradict the overflow hypothesis (OH), which postulates that the overflow of photo-synthase is the main driver of lipid and/or starch accumulation and is frequently discussed to explain increased carbon storage in photosynthetic microbes under stress conditions (Juergens, Disbrow, & Shachar-Hill, 2016; Neijssel & Tempest, 1975; Tan & Lee, 2016): indeed, substantial compromise in PSII activities at both transcriptional and phenotypic levels at early growth phase and the upregulation of enzymes associated with the accumulation of lipid throughout entire growth stages clearly suggest that the overflow of organic photo-synthase ab initio was not the main driver of high lipid accumulation under salinity stress. Rather, our results identified the pulling of the acetyl-CoA precursor generated from glycolysis towards lipid synthesis as a major driver of lipid accumulation; accordingly, the redirection of storage carbon likely resulted in the seeming conversion of carbohydrate to lipid as observed in the proximate analysis of harvested biomass.…”
Section: Discussioncontrasting
confidence: 73%
“…In addition to acetyl-CoA precursors, the synthesis of glycerolipid necessitates NADPH as a cofactor (Tan & Lee, 2016). Being an electron donor, NADPH is synthesized along with ATP during the light reaction of photosynthesis, and has been acknowledged for its role as an oxidative stress mediator (Valderrama et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in microalgae have shown that N deprivation induces de novo FA biosynthesis and results in an accumulation of significant amounts of storage lipids in the form of TAG (Li et al, 2012a(Li et al, , 2014Yang et al, 2013;Tan and Lee, 2016). The core building block of FA biosynthesis, acetyl-CoA, is generated by one of two types of multienzyme pyruvate dehydrogenase complex, plastidial (pPDHC) or mitochondrial PDHC.…”
Section: Nitrogen Accessibility Affects Fa Biosynthesismentioning
confidence: 99%
“…Apparently for SDEC-11, clear thylakoids in chloroplast were observed after phytohormones treatment, which could be another reason for the higher lipid content in GIB-treated groups. Moreover, Tan and Lee [57] summarized that the generation of NADPH could mainly derive from the metabolism of starch. Compared with ultrastructural cells in ADE-KW control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Over-reduction will occur in the photosynthetic electron transport chain due to richness of NADPH, which could lead to some reactions with highly reduced products, such as lipid synthesis [58]. In addition to carbon supply, de novo FA synthesis also requires a continuous provision of reducing power in the form of NADPH [57]. It may be the efficient stimulation by GIB of chlorophyll in algae that ultimately leads to an increase in lipid accumulation.…”
Section: Resultsmentioning
confidence: 99%